INNOVATIVE METHODS OF ORGANIZING STUDENTS’ INDEPENDENT LEARNING ACTIVITIES IN THE DIGITAL EDUCATION ENVIRONMENT (Web of Teachers: Inderscience Research, 2026)
The rapid transformation of higher education under the influence of digital technologies has fundamentally reshaped the conceptualization and organization of students’ independent learning activities. This article explores innovative pedagogical approaches aimed at enhancing learners’ autonomy, cognitive engagement, and self-regulated learning within digital education environments.